Critical Analysis of Matthew Lipman's Multidimensional Thinking In Philosophy for Children (P4C) from The Perspective of Islamic Thought - Mohammad Muslih; Nurul Inayah (University of Darussalam Gontor, Indonesia, 2026)
This study employs a critical descriptive-comparative approach to examine Matthew Lipman’s concept of multidimensional thinking in Philosophy for Children (P4C) from the perspective of Islamic thought. In the context of global education that prioritizes STEAM disciplines to promote Higher Order Thinking Skills (HOTS), Lipman’s framework highlights critical, creative, and caring thinking as core dimensions. However, Islamic epistemology offers a more holistic understanding of thought. Using qualitative analysis, this study first reconstructs Lipman’s ideas based on Thinking in Education and Philosophy Goes to School, alongside classical Islamic concepts of ‘aql (intellect), qalb (heart), and nafs (soul). A comparative analysis is conducted to identify key similarities and differences, followed by a critical evaluation of the epistemological limitations of Lipman’s model. The findings indicate that, in Islam, thinking transcends rational processes and encompasses spiritual and ethical dimensions. While Lipman’s model is valuable in cultivating reflective thinking, it remains largely secular. Islam, by contrast, integrates reason, intuition, and divine consciousness. This study concludes that multidimensional thinking in Islam reflects the principle of tawḥīd al-‘ilm, offering a more integrated framework that unifies intellectual, moral, and spiritual dimensions of knowledge.